NSCAs Performance Training Journal - Conditioning Fundamentals (NSCAs Performance Training Journal, 2011)
Juan Gonzalez: Eccentric Training for Distance Runners - Downhill running promotes eccentric muscle activation. The effects of downhill running on distance runners are examined and examples of training exercises are offered. Chat Williams: Flexibility Training: Incorporating All Components of Fitness - An introduction to the importance of fl exibility training is defi ned. The research behind fl exibility training and guidelines for incorporating it into a program are examined. Kyle Brown: Using Whole Body Integrated Multi-Planar Exercises For Baseline Conditioning - Whole body integration utilizes movements that incorporate the entire body instead of just one muscle or muscle group. This concept will be applied to everyday usefulness and examples of exercises employing whole body integration will be presented. Debra Wein; Caitlin O. Riley: Protein Requirements for Athletes - There is considerable debate regardingthe proper intake of protein for athletes. The current recommendations for protein ingestion are presented. Alternate protein supplements are also examined.